Chemistry Online Distance Learning during the Covid-19 Outbreak: Do TPACK and Teachers' Attitude Matter? (Jurnal Pendidikan IPA Indonesia, 2021)
The COVID-19 outbreak has made many countries decide to close schools to prevent the spread, including Indonesia. This leads to online distance learning. Furthermore, online distance learning is carried out by teachers suddenly without prior preparation. Therefore, the teachers' Technological, Pedagogical, Content Knowledge (TPACK), and attitude to conduct online distance learning are crucial. Thus, this study intends to identify chemistry teachers’ TPACK and attitude in online distance learning during the COVID-19 outbreak. Purposed-design survey method was used with 109 participants in Java, Indonesia. The data were collected using online questionnaires then analyzed quantitatively using factor analysis and qualitatively based on the teachers’ response to online distance learning during the COVID-19. The questionnaire used consisted of 36 close-ended statements with a Likert scale and 10 open-ended questions to find out challenges and opportunities for implementing chemistry online distance learning. The results show that the teachers try to adapt their way of teaching and assessment by using various technology platforms for online distance learning. The attitude and TPACK of the teachers tend to be positive in responding to online distance learning even though some senior teachers have a negative tendency to the aspects of attitude and technological knowledge. It can be implied that training in the use of various technologies, and enhancement of chemistry teachers’ TPACK skills are needed to produce better online distance learning. These results are expected to provide an overview of the challenges and opportunities of online distance learning in chemistry during or beyond the COVID-19 outbreak.